Identification of distinct cytomorphologic features in the diagnosis of NIFTP at the time of preoperative FNA: Implications for patient management. Issue 11 (21st August 2017) - Chandler, Jocelyn B.; Colunga, Monica; Prasad, Manju L.; Callender, Glenda G.; Quinn, Courtney; Chhieng, David; Adeniran, Adebowale J.
Abstract : BACKGROUND: A major reclassification occurred with the redesignation of noninvasive encapsulated follicular variant of papillary thyroid carcinoma as noninvasive follicular thyroid neoplasm with papillary‐like nuclear features (NIFTP) due to its indolent nature. The aim of this study was to determine whether distinct cytomorphologic features could be identified on preoperative fine‐needle aspiration (FNA) when NIFTP cases were compared with invasive follicular variant of papillary thyroid carcinoma (FVPTC) subtypes. METHODS: Thyroid resection cases with the diagnosis of FVPTC from 2012 to 2016 were reclassified as NIFTP, invasive encapsulated follicular variant of papillary thyroid carcinoma (IEFVPTC), and invasive FVPTC subtypes. Corresponding FNA specimens were retrieved and retrospectively reviewed. A univariate analysis using Fisher's exact test was performed to determine any differences in the frequencies of various cytomorphologic features among NIFTP, IEFVPTC, and FVPTC cases. A multivariate analysis was performed to identify any independent salient features that would be helpful in differentiating NIFTP from its invasive counterparts. RESULTS: The study population consisted of 93 cases, including 51 cases of NIFTP, 21 cases of IEFVPTC, and 21 cases of infiltrative FVPTC. Demographics such as age, sex, and tumor size were comparable across the 3 groups. A predominantly microfollicular pattern, an absence of nuclear pseudo‐inclusions, and less frequent nuclear elongations and grooves were significantly more likely to be associated with NIFTP versus its invasive counterparts. The absence of nuclear pseudo‐inclusions and the presence of a microfollicular pattern were the only independent predictors of a NIFTP diagnosis. CONCLUSIONS: This study demonstrates that NIFTP cases have distinguishing cytomorphologic characteristics in comparison with invasive FVPTC cases. Therefore, a preoperative cytologic evaluation provides clues that can aid in the distinction between NIFTP and its invasive counterparts. Cancer Cytopathol 2017;125:865–75. © 2017 American Cancer Society. Abstract : The findings of this retrospective study demonstrate that cytomorphologic features differ between noninvasive follicular thyroid neoplasms with papillary‐like nuclear features and invasive follicular thyroid carcinomas. The recognition of these subtle cytomorphologic features could help to improve the diagnosis at the time of preoperative fine‐needle aspiration, and this could affect surgical decision making for follicular thyroid tumors.